THE SPECIAL FORCES BIBLE - Stilwell, Alexander (Chartwell Books, 2013)
The Special Forces Bible is the inside guide to the operations, training, and equipment of the world's military elite. Special Forces are elite military highly-trained teams from the army, navy, or air force, who are recruited to take on the most dangerous confidential missions. Trained to exacting standards, they are prepared for anything, anytime, anywhere. This book details over 80 specialized tactics that the forces employ to carry out their duties: arming and disarming bombs underwater; defensive and offensive driving; free-falling from airborne helicopters; and HALO parachuting from planes 35,000 feet (11,000 m) in the air. The topics cover include attack skills and artillery, defensive and offensive driving, tracking and survival tactics, and infiltration and extraction by air, land, and sea. With real-life cases and illustrations, this book blows the lid on the forces' demanding search and rescue missions and covert operations. The Special Forces Bible is the inside guide to the operations, training, and equipment of the world's military elite.